Creating Culturally Competent Teachers in Higher Education As a Consequence of Cultural Immersion - Antony, Pavan John.; Vaughn-Shavuo, Fayth (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents evidence of a longitudinal study in teacher preparation utilizing a threefold multicultural (TFM) model of immersion. It establishes the need for culturally responsive teachers in classrooms, and outlines a proven model that can be employed to prepare them. Through the TFM model elements, pre-service teacher candidates participated in class-based, cohort fieldwork experience, and reflective journal writings and discussions. Evidence was gathered from pre- and post-questionnaires, interviews, classroom discussions, and journal writings, along with the inclusion of student voices. Pre-service teacher attitudes, beliefs, and degree of cultural responsiveness changed post-study, and candidates became more effective in the classroom, highlighting the effectiveness of the TFM model. This book is an invaluable resource for universities, under- and postgraduate students, and teachers across the globe as it provides a teacher preparation fieldwork model that helps to prepare culturally responsive teachers for children in any classroom.
Culturally Diverse Communities on Long Island in the United States -- Truth, Racial Healing, and Transformation (TRHT) on college campuses -- The Tri-Fold Multicultural Model: A Cultural Immersion Approach -- Attitudinal Changes Among Teacher Candidates: The Power of the TFM Model -- Higher Education and Community Based partnerships during COVID - 19: A Case Study of the VIRTUAL P.E.A.C.E. Afterschool Program, Inc. -- Student and Teacher Candidate Experiences during the COVID-19 -- Stories of Transformation -- Voices of Student Observers and Teacher Candidates.-Voices of Current Teachers during COVID-19.
Keywords: Teachers-Training of; Education, Higher; Education and state; Teaching and Teacher Education; Higher Education; Educational Policy and Politics